Use of Open Source Hardware and Software Platforms to Quantify Spectrally Dependent Differences in Photochemical Efficiency and Functional Absorption Cross Section within the Dinoflagellate Symbiodinium spp. - Hoadley, Kenneth D.; Warner, Mark E. (Frontiers in Marine Science, 2017)
Active chlorophyll a fluorescence is an essential tool for understanding photosynthetic activity within cnidarian/dinoflagellate symbioses. Fluorescence measurement is typically achieved by utilizing a blue or red monochromatic excitation light source. However, algal photosynthetic pigments can differ in their absorption spectra, potentially leading to excitation wavelength dependent measurements of maximal and light acclimated PSII photosynthetic quantum yield (Fv/Fm or Fq’/Fm’) and functional absorption cross section (PSII or PSII’). Here we utilized an open source hardware development platform to construct a multispectral excitation fluorometer to assess spectrally dependent differences in photochemistry within four different Symbiodinium species (two of each ITS2-type A4 and B1). Multivariate analysis of light acclimated photochemical signatures showed separation between most alga types. These spectrally dependent differences in light acclimated PSII efficiency and PSII functional absorption cross section likely reflect changes in light harvesting compounds, their connectivity to the PSII reaction centers and the balance between photochemical and nonphotochemical fluorescence quenching. Additionally, acclimation to low (20 mol photons m-2 s-1) and high (200 mol photons m-2 s-1) light conditions was examined in two of these symbionts types (ITS-2 type A4 and B1) As expected, chlorophyll a cell-1 decreased under high light acclimation in both symbionts. However, only A4 saw a subsequent reduction in absorbance whereas cellular volume decreased in the B1 (S. minutum) symbiont. In response to high light acclimation, Fv/Fm was significantly lower at all excitation wavelengths for the B1 symbiont where as efficiencies remained the same for A4. However, high-light acclimated Fq’/Fm’ levels decreased in both symbionts, but only when measured using the 615nm or 625nm excitation wavelengths. Non-photochemical quenching within the antennae bed was downregulated under high light acclimation in the A4 symbiont, but only when measured using the 505nm and 530nm excitation wavelengths. Such changes in Fq’/Fm’ and antennae bed quenching highlight the benefits of spectrally resolved photochemical measurements. Additionally, the utilization of Arduino and Bitscope hardware exemplifies the potential of open source development platforms for construction of highly customizable instrumentation for photosynthetic research.